(untitled) (Studia Prawnicze / The Legal Studies, 1975)
W momencie zawierania umowy o pracę musi zostać określone prawo pracownika do wynagrodzenia. Na przełomie XVIII i XIX w. wynagrodzenie ustalono wyłącznie techniką umowną. Powstanie i rozwój ruchu zawodowych doprowadziły do wytworzenia się praktyki zawierania układów zbiorowych pracy. Ustalenie wynagrodzenia za pracę może się odbywać także techniką ustawową. We współczesnej praktyce stosunków pracy stosuje się w celu ustalenia wynagrodzenia kombinacją wszystkich opisanych technik. Dzieje się tak zwłaszcza w krajach kapitalistycznych. Zagadnienie roli techniki umownej ustalania wynagrodzeń za pracę staje się szczególnie doniosłe i interesujące w warunkach szeroko rozwiniętej normatywnej regulacji płac w państwie socjalistycznym. When an employment contract is concluded, the employee’s entitlement to remuneration must be determined. In the late 18th and early 19th centuries, remuneration was established solely by contractual technique. The rise and development of the labour movement led to the emergence of the practice of collective bargaining. Determination of the remuneration for the work can also take place through a statutory technique. In contemporary industrial relations practice, a combination of all the techniques described is used to determine remuneration. This is particularly the case in capitalist countries. The issue of the role of the contractual technique for determination of remuneration becomes particularly momentous and interesting under the conditions of an extensively developed normative wage regulation in a socialist state.